Analisis Resiko Berdasarkan Metode Risk Based Inspection (Rbi) Pada Scrubber Vessel - Dika Rahayu Widiana, Teguh Wahyudi (Techno Bahari, 2016)
Chemical industrial activities in PT. X involves scrubber vessel to treat dust from the dryer and granulator so that air is disposed comply the threshold value. Therefore scrubber vessel's reliability is important in air pollution prevention activities in this industry. Implementation of inspection program is one of the key to maintain the system reliability. Implementation of inspection program to maintain the system reliabilty has evolved by the time. Traditional inspection program only based on perspective of industrial practices and not based on the actual condition of component in conducting inspections. Risk Based Inspections (RBI) involves the planning of an inspection on the basis of the information obtained from a risk analysis of the equipment. The purpose of the risk analysis is to identify the potential degradation mechanisms and threats to the integrity of the equipment. Risk analysis also has purpose to assess the consequences and risks of failure. This final project will analyze the risk of scrubber vessel failure based on RBI 581. Based on the analysis, the third scrubber vessel has probability with value 0,00009 failure/year and be categorized 2. Consequences of toxic area is 82483.78 ft2 and be categorized E so the risks are classified as medium-high 2E.